1998
DOI: 10.1002/(sici)1099-0496(199803)25:3<147::aid-ppul3>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

The anaerobic threshold in cystic fibrosis: Comparison of V‐slope method, lactate turn points, and Conconi test

Abstract: Summary. Physical exercise can improve sputum clearance in patients with cystic fibrosis (CF). To set up individual training protocols it is desirable to know the anaerobic threshold (AT). Established methods such as blood lactate measurements and ergometry can only be performed in specialized centers. Conconi showed that the heart rate threshold (HRT), i.e., the deflection point from the linear relationship between work load and heart rate, correlated significantly with the AT in healthy adults. To assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…However, there is little data concerning lactate accumulation during exercise in CF, although several small studies in subjects with milder disease have shown that lactate accumulation occurs [16][17][18][19]. There is very little information concerning symptom limitation during exercise in CF.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…However, there is little data concerning lactate accumulation during exercise in CF, although several small studies in subjects with milder disease have shown that lactate accumulation occurs [16][17][18][19]. There is very little information concerning symptom limitation during exercise in CF.…”
supporting
confidence: 52%
“…Several smaller studies have included lactate measurement in the assessment of peak exercise, and have shown that CF subjects do generate a rise in blood lactate on progressive exercise [16][17][18][19]. The present authors found raised lactate levels at peak exercise in CF patients across the full range of pulmonary disease severity, with those in the middle/ moderate group achieving very similar peak concentrations to controls.…”
Section: Discussionmentioning
confidence: 99%
“…The VAT is a useful, reproducible method with which to determine aerobic fitness in healthy adults and children, as well as in CF, and especially for those who cannot perform a maximal incremental cycling test [24,25]. In healthy untrained people, the VAT occurs at intensities between 50-60% of V9O 2 ,peak and rarely surpasses 60% of V9O 2 ,peak [26].…”
Section: Discussionmentioning
confidence: 59%
“…11 Estimation of the anaerobic threshold by the V-slope method, which was used for some subjects, may have influenced breathing reserve index values at the anaerobic threshold, but not at W peak . 23 Our results show that breathing reserve index at W peak is a useful indicator of ventilatory limitation, even in younger children.…”
Section: Discussionmentioning
confidence: 99%